Thermo-mechanical analysis of laminated composites shells exposed to fire. (15th February 2022) - Pacheco-Blazquez, R.; Di Capua, D.; García-Espinosa, J.; Casals, O.; Hakkarainen, T.
Abstract: This paper describes the research performed within the scope of H2020 project FIBRESHIP in the development and validation of a thermo-mechanical model to assess the fire performance of composite structures. A one-dimensional thermal model with pyrolysis is used to obtain the temperature profile across the thickness, and later, introduced in the thermo-mechanical model with a quadrilateral shell element approach. The composite constitutive model employed is the so-called Serial/Parallel Rule of Mixtures (SPROM) which has been modified to introduce the effect of the thermal deformation. A set of experimental tests are then used to validate the correctness of the numerical method proposed. The experimental data used to validate the thermal model is the classic Henderson experimental test. The thermo-mechanical coupling is validated against an original vertical furnace test of an FRP ship's bulkhead, following on the 2010 FTP Code standards. These validations demonstrate the correctness and accuracy of the proposed decoupled thermo-mechanical formulation. Highlights: Modification of the SPROM theory in order to take thermal expansion. Obtainment of the thermo-chemical–mechanical degradation of each constituent material separately. The method is validated against own experimental data from the 2010 FTP Code standard.